2020
DOI: 10.1111/jpn.13427
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary pomegranate peel (Punica granatum L.) and Aloe vera gel (Aloe barbadensis miller) supplementation on testicular antioxidant biomarkers and spermatogenesis enzymes in mature V‐Line rabbit bucks

Abstract: Rabbit meat is considered as an economic source of white meat, increasing its production is limited by the buck fertility, since one rabbit can be used to inseminate up to 15 female. The aim of the current study is to enhance male rabbit fertility by using dietary antioxidants including Aloe vera gel (AVG) and pomegranate peels (PP). In a 60 days experiment, 48 V‐Line 5‐month‐old rabbit bucks of average body weight (2,300 ± 20) kg were allocated into four dietary treatments (n = 12/group) as follow: CON (fed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
(35 reference statements)
2
5
0
Order By: Relevance
“…The concentrations of TAC and SOD from all the treatments were significantly higher compared with those of the control group. This follows the same trend as the findings of Bakeer et al, (2020) and Guo et al, (2008), who reported that the plasma antioxidant capacity increased when subjects consumed pomegranate juice; moreover, reduced MDA levels are evidence of reduced lipid peroxidation. Therefore, the antioxidant activity of pomegranate seems to be a result of its high contents of phenolic compounds (Moneim et al, 2011).…”
Section: Discussionsupporting
confidence: 89%
“…The concentrations of TAC and SOD from all the treatments were significantly higher compared with those of the control group. This follows the same trend as the findings of Bakeer et al, (2020) and Guo et al, (2008), who reported that the plasma antioxidant capacity increased when subjects consumed pomegranate juice; moreover, reduced MDA levels are evidence of reduced lipid peroxidation. Therefore, the antioxidant activity of pomegranate seems to be a result of its high contents of phenolic compounds (Moneim et al, 2011).…”
Section: Discussionsupporting
confidence: 89%
“…Semen samples were immediately assessed for pH (pH probe pH600, Milwakuee), semen volume, mass motility using a light microscope with thermostatically controlled hot stage adjusted at 38-40 C (Olympus, USA; and score 0-5 was used), individual motility (%), sperm viability (%), sperm abnormalities (%), and sperm concentration (The number of spermatozoa present on both sides of Neubauer haemocytometer slide (Marienfeld, USA). The semen evaluation process is detailed in our former report (Bakeer et al 2021).…”
Section: Semen Samples Collection and Evaluationmentioning
confidence: 99%
“…One economic strategy to reduce feed cost while maintaining the optimal production level is to find dietary alternatives to the expensive and unavailable dietary ingredients. For instance, FM availability is limited in some parts of the world due to its high price and limited availability (Ogello et al, 2014; Bakeer et al, 2021). Therefore, in the current study, we investigated the replacement of FM with POS with or without betaine supplementation in Nile tilapia fish diet.…”
Section: Discussionmentioning
confidence: 99%